Prevalence of Salmonella infection in naturally infected layer of birds in Bangladesh (Bangladesh Veterinarian, 2011)
The seroprevalence, cultural prevalence and pathological study of Salmonella infections in chickens of selected layer farms of Birgonj Upazila (Sub-district), Dinajpur were determined. A total of 175 blood samples were tested randomly by locally prepared Salmonella coloured antigen for seroprevalence study. Out of 96 cloacal swabs, 80 samples from live birds (36 from seropositive and 44 from seronegative) and 16 samples from dead birds were collected to determine the cultural prevalence of Salmonella organisms. Postmortem examination was done in 16 dead birds. Using whole blood agglutination test (WBA) with locally prepared Salmonella Pullorum coloured antigen, the overall seropositive prevalence was 46.2%. The seroprevalence decreased with age of birds. The cultural prevalence in seropositive was 33.3% and in seronegative 22.7%. In dead birds, the cultural prevalence using cloacal swab was 25%. A total 26 Salmonella were isolated, 27% Salmonella Pullorum, 58% Salmonella Gallinarum and 15% paratyphoid group of Salmonella. Isolation rate of Salmonella from cloacal swabs was significantly higher in seropositive than seronegative group. Grossly, the livers were friable, with bronze discolouration and necrotic foci, there was severe congestion in the lung, congested haemorrhagic egg follicles with stalk formation and enlarged discoloured spleen. Microscopically, there was focal necrosis and degeneration with leukocytic infiltration in liver, congestion and pneumonic lesions in the lung and various degrees of catarrhal to haemorrhagic enteritis in the intestine. In the egg follicles, congestion and haemorrhage with leukocytic infiltration and enlarged spleen with white necrotic foci were detected. In future, isolated Salmonella organisms may be used for vaccine production, serotyping and antibiotic sensitivity test. DOI: http://dx.doi.org/10.3329/bvet.v28i1.8809   Bangl. vet. 2011. Vol. 28, No. 1, 8-18